Strategi Guru Mata Pelajaran Ilmu Pengetahuan Sosial (IPS) Dalam Menumbuhkan Sikap Sosial Siswa Di Madrasah Sanawiyah (Mts) Roudlotur Rosmani Kota Bengkulu - Annisa Seftiansari; Moch Iqbal; Saepudin (JPT : Jurnal Pendidikan Tematik, 2025)
The purpose of this study is to determine the strategy of social studies teachers in fostering social attitudes at Mts Roudlotur Rosmani, Bengkulu City. This type of research is field research with a qualitative approach. Data collection techniques use observation, interviews, and documentation. Based on the findings and results of data analysis, it can be concluded that, the strategy of social studies teachers in fostering social attitudes of students at Mts Roudlatur Rosmani, the strategy begins with an explanation regarding the importance of having skills in oneself, how to cultivate and improve social attitudes, and the benefits of having social skills. In addition, the social studies teacher not only explains the theory, but also applies what the theory is intended to be. Social studies teachers improve students' social attitudes, it will be easier to apply. As the social studies subject itself, trying to shape and foster students' characters to be much better. inhibiting factors regarding the strategy of social studies teachers in fostering social attitudes at MTs Roudlotur Rosmani, Bengkulu City, namely internal factors when students have no desire or intention to change social attitudes, then teachers find it difficult to foster social attitudes to students. Meanwhile, external factors include providing good attention and understanding to students in supporting social activities and encouraging them in the learning process, providing good material at each meeting.